The impact of living alone on older adults’ mental health and the mediating role of healthy diet - Zheng, Jichao; Ni, Zeqiang (Frontiers in Psychiatry, 2025)
BackgroundMore than 30 million older people in China live alone. Research has shown that living alone can lead to poor mental health and that there are mediating variables, such as healthy diet, between living alone and mental health. Therefore, it is important to examine the role of these mediating variables between living alone and mental health to help us develop cost-effective mental health interventions.MethodsWe used the multiple regression method in the R software to test the effect of living arrangements on depression by placing the living arrangements variable, the covariates, and the healthy diet variables into the regression equation. We then used the structural equation method with the R software package lavaan to derive the path coefficients of living arrangements on depression scores through the three mediating paths of fruits, vegetables, and nuts consumption. We used bootstrapping to derive confidence intervals for the coefficients.ResultsMultiple regression results showed that the coefficient of the effect of living alone on depressive symptoms was 1.02. At the same time, all three variables of a healthy diet can alleviate depression, i.e., consuming more fruits, vegetables, and nuts helped to reduce depression scores among older adults. In the mediation analysis, living alone affects the mental health of older adults through three channels, namely, fruit consumption, vegetable consumption, and nuts consumption, respectively, and the indirect effects of these three channels accounted for 15.47% of the total impact of living alone on depression scores of older adults, with vegetable intake having the most significant effect on depression scores, accounting for 8.35% of the total impact, followed by nuts intake and fruits intake.ConclusionOlder people living alone are a vulnerable group with poor mental health and require a variety of interventions to improve their mental health. Healthy eating is one possible avenue of intervention; the Government should take diversified initiatives to enhance the healthy diet of older persons living alone.